Spectrophotometric Estimation of Drotaverine Hydrochloride from Tablets - SHIRKHEDKAR, A.A.; UPASANI, G.H.; SURANA, S.J. (Asian Journal of Chemistry, 2010)
A simple, rapid, accurate and precise UV-spectrophotometric method has been developed for the quantitative estimation of drotaverine hydrochloride in bulk and tablets. Proposed method involves quantitative estimation of drotaverine hydrochloride at 303 and 354 nm. The linearity was observed in the concentration range of 4 - 24 μg/mL at both the wavelengths. The % label claim was found to be in range of 99 - 99.7% at both the wavelengths. The results of analysis have been validated statistically and by recovery studies.